Photocatalytic Degradation of Methylene Blue and Antibacterial Activity of Mesoporous TiO2-SBA-15 Nanocomposite Based on Rice Husk - Eid H. Alosaimi; Ibrahim Hotan Alsohaimi; Talal E. Dahan; Qiao Chen; Ayman Abdelaziz younes; Belal El-Gammal; Saad Melhi (Adsorption Science & Technology)
Concerns have been increased regarding the existence of pollutants in environmental water resources and their risks to the ecosystem and human society. TiO2 photocatalyst is considered as an effective photocatalyst to remove the pollutants. Herein, the mesoporous TiO2-SBA-15 was prepared using the rice husk extract as the silica source. The fabricated nanocomposites were characterized using FTIR, small and wide angle XRD, Raman spectroscopy, UV-vis, BET surface area analysis, and HRTEM. The photocatalytic efficiency of the composites for the degradation of methylene blue (MB) has been evaluated under UV irradiation. Interestingly, due to the excellent dispersion of TiO2 on the wall of SBA-15 and good hydrophilicity, the nanocomposites displayed a good catalytic activity. The higher photodegradation performance was achieved by the composite containing 10 wt% TiO2 by which the MB was fully degraded within 15-20 min of irradiation. Besides, TiO2-SBA-15 could effectively inhibit the growth of Gram-positive and Gram-negative bacteria. These results offer a practical and economic approach in the environmental management industries.